Local adaptative strategies for coping with drought stress in Neltuma alba (Leguminosae, Caesalpinioideae) are associated with the timing of leaf senescence - Lopez Lauenstein, Diego; Vega, Carmen Delcira; Verga, Anibal; Lascano, Hernan Ramiro; Marchelli, Paula (Springer, 2025)
Drought stress is a significant abiotic factor that limits plant growth and has led to widespread tree mortality worldwide. As climate change predicts longer, more severe, and unpredictable drought periods in subtropical regions, understanding how forest ecosystems cope with such stress becomes critical. This study focuses on Neltuma alba, a drought-tolerant tree species commonly found in the Gran Chaco Americano region of South America. We investigated the coexistence of different behaviors to cope with drought stress in N. alba and searched for signals of local adaptation in its populations. Using a combination of macroscopic leaf morphological traits and genetic (molecular) information in common garden experiments, we identified four behaviors in N. alba plants for coping with drought stress.